Rutting load equivalency factors of heavy vehicles operating in the Sothern part of Malaysian peninsula - Yassenn O.M.; Endut I.R.; Hafez M.A.; Ishak S.Z. (Springer Verlag, 2023)
Management science; Pavements; And rutting; Flexible pavement designs; Flexible pavements; Heavy vehicle; Malaysia; Malaysians; Traffic volumes; Weight in motions; Vehicles